Factors affecting the happiness level in Southeast Asia countries with a multilevel approach - DHEWI, OKTIVA RAHMAWATI; KISMIANTINI, KISMIANTINI (Universitas Syiah Kuala, 2024)
The level of the populations well-being can be measured by using a subjective well-being indicator which is called happiness, which can be affected by various factors from individuals. However, the background of individuals in a group cannot be ignored. Therefore, this study aimed to determine the factors that affect the level of happiness in Southeast Asian countries at the individual and country levels. Data came from World Value Survey (WVS) Wave 7 with 11,387 individuals from the Philippines, Indonesia, Malaysia, Myanmar, Singapore, Thailand, and Vietnam. Data were analyzed using an ordinal response multilevel model with the level of happiness as a response variable. The results showed that the happiness level was affected by gender, marital status, health status, income, religiosity, education level, life satisfaction, and freedom of choice. However, age at the individual level and variables at the country level did not affect the happiness level.